APPLICATION OF MARRIAGE LAW SUBJECT, STUDENT EDUCATION TO PREMARITAL SEX BEHAVIOR - Marpi, Yapiter (Proceeding of International Conference on Islamic Education (ICIED); Vol 5 No 1 (2020): Proceeding of International Conference on Islamic Education (ICIED), 2021)
This research paper aims to analyze the study of the subject of marriage law in students on premarital sex behavior in Jakarta, at the Faculty of Law, University of Jakarta and the factors that influence it. The maturity of physical and biological functions occurs. Premarital sexual behavior is all behavior that is driven by sexual desire, whether done alone, with the opposite sex or the same sex without any marriage ties. The basic method used in this research is descriptive method using mixed methods approach, and sequential explanatory strategy. The data collection technique was carried out using a questionnaire to 75 students in the class randomly. Quantitative data analysis was carried out using a normative comparative study as a complement to the discussion and carried out a qualitative analysis. The results showed that the factors that influenced student behavior were student attitudes towards premarital sex, family, and the media. So from a study of the marriage law course, students will understand the legal aspects of marriage and the negative effects of marriage and the rules of marriage so that they always keep away from free sex and get closer to God to carry out sex programs according to religious orders and legal state rules.